Differentiation of food protein-induced enterocolitis syndrome and necrotizing enterocolitis in neonates by abdominal sonography - Yiyi Guo; Shuyu Si; Zhifang Jia; Xiaoming Lv; Hui Wu (Elsevier, 2021)
Objectives: To summarize and differentiate abdominal ultrasound findings of necrotizing enterocolitis and food protein-induced enterocolitis syndrome. Methods: From January 2017 to December 2018, the abdominal ultrasound results of 304 cases diagnosed necrotizing enterocolitis or food protein-induced enterocolitis syndrome were retrospectively analyzed. The presence of pneumatosis intestinalis, portal venous gas, bowel wall thickening, intestinal motility, focal fluid collections and hypoechoic change of gallbladder wall were calculated, and the results were compared and analyzed. Results: Pneumatosis intestinalis, portal venous gas, bowel wall thickening, intestinal motility weakened/absent, focal fluid collections and hypoechoic change of gallbladder wall can be found in both necrotizing enterocolitis and food protein-induced enterocolitis syndrome infants. However, in infants with necrotizing enterocolitis, intestinal motility was weakened/absent in whole abdomen, and in food protein-induced enterocolitis syndrome, it only involved isolated segment of bowel. The positive rates of above signs in necrotizing enterocolitis infants were significantly higher than those in food protein-induced enterocolitis syndrome (p < 0.01). Moreover, it was observed that the rate of weakened intestinal motility besides the lesion segment of bowel in necrotizing enterocolitis infants was 100%, and in food protein-induced enterocolitis syndrome infants, it was 0%, which is supposed to be a main sign for identification. Conclusion: In the early stage, abdominal ultrasound can be used to differentiate necrotizing enterocolitis and food protein-induced enterocolitis syndrome.